LEGALITAS PENGGUNAAN OBAT SEBAGAI TERAPI PENYEMBUHAN PENYAKIT YANG DISEBABKAN OLEH COVID-19 DI MASA PANDEMI; STUDI TERHADAP PENGGUNAAN INVERMECTIN - Gunawan Widjaja; Annisa Purwo Hastuti (CV. ADIBA AISHA AMIRA, 2022)
There is no denying that the Covid-19 outbreak has become one of the most frightening diseases. One of them is the large number of use of drugs that have not been through clinical trials. One of them is Ivermectin. This paper describes several things that need to be known until a drug can be circulated and the meaning of granting the distribution permit. The discussion shows that Ivermectin does have a marketing authorization, however, Ivermectin, in that distribution permit, has never been indicated for the treatment of diseases as a result of Covid-19. The distribution permit must also be accompanied by Good Manufacturing Practices (GMP) and circulated in Good Drug Distribution Methods (CDOB)